Dweller in shadows : a life of Ivor Gurney : war poet, composer, asylum patient - Kennedy, Kate, 1977- (Princeton University Press, 2021)
"Ivor Gurney (1890-1937) was a composer and poet. Originally a student of music, he took up poetry in the trenches of the First World War, and was working on what would be his first volume of verse when, in 1917, he suffered wounds to the shoulder; and it was just before publication of this volume, Severn & Somme, that he was gassed at Passchendaele. After his return to Britain he resumed his musical studies, availing himself briefly of the tutelage of Ralph Vaughan Williams, and quickly found outlets for his compositions. There is some debate about whether or not his subsequent mental illness was a consequence of the horrors and sufferings of the war; but mental illness marked the rest of his life, and indeed from about 1922 until his death he was institutionalised. In his last years he literally believed that he was William Shakespeare. He nevertheless continued to produce poems and musical compositions in prolific fashion, and his works in both areas are read and performed, respectively, to this day"--